Highways versus pipelines: contributions of two fungal transport mechanisms to efficient bioremediation. Issue 2 (24th October 2012) - Banitz, Thomas; Johst, Karin; Wick, Lukas Y.; Schamfuß, Susan; Harms, Hauke; Frank, Karin
Summary Based on experimental studies, two different fungus‐mediated transport mechanisms have been suggested to facilitate the bacterial degradation of organic soil pollutants: bacteria may use liquid films around fungal hyphae for quick dispersal ('fungal highways'), and fungi may take up and translocate pollutants through their mycelial network ('fungal pipelines'). Both mechanisms are anticipated to enhance the bioavailability of pollutants to degrading bacteria. Using a microbial simulation model, we therefore investigated their respective efficiency in increasing biodegradation performance. We analysed networks that act either as bacterial dispersal vectors or as pollutant translocation vectors or as a combination of both. Our results suggest that each mechanism can improve biodegradation performance. The degree of improvement, however, varies distinctly depending on the environmental conditions, and is even negligible under certain conditions. Mycelial networks acting as 'highways' allow bacteria to overcome motility restrictions and reach remote areas, whereas networks acting as 'pipelines' may initiate degradation by bringing remote pollutants to bacteria. As a consequence, highest biodegradation improvements often emerge from the combination of both mechanisms. We conclude that 'fungal highways' as well as 'fungal pipelines' should be considered for developing novel bioremediation strategies based on fungus‐mediated transport in soils.